Endogenous Estrogen Metabolites as Biomarkers for Endometrial Cancer via a Novel Method of Liquid Chromatography-Mass Spectrometry with Hollow Fiber Liquid-Phase Microextraction - Zhao, H.; Jiang, Y.; Liu, Y.; Yun, C.; Li, L. (Hormone and Metabolic Research, 2015)
Increased levels of endogenous estrogens and their metabolites are well-known risk factors of endometrial cancer. The aim of this study was to quantitatively assess the potential for estrogen metabolites to serve as biomarkers of endometrial carcinogenesis. The following estrogen metabolites were evaluated: 2-hydroxyestradiol (2-OHE2), 2-hydroxyestrone (2-OHE1), 4-hydroxyestradiol (4-OHE2), 4-hydroxyestrone (4-OHE1), 16α-hydroxyestrone (16α-OHE1), 2-methoxyestradiol (2-MeOE2), and 2-methoxyestrone (2-MeOE1). The low content of estrogen metabolites in urine makes their measurement difficult. To address this issue, we developed a rapid, sensitive, specific, and accurate liquid chromatography-mass spectrometry (LC-MS) method, with hollow fiber liquid-phase micro-extraction (HF-LPME) for an enriched pretreatment of the sample and for the simultaneous quantification of estrogens and their metabolites in the urine samples of 23 post-menopausal female endometrial cancer patients and 23 post-menopausal healthy female controls. The levels of estrogens were found to differ between the endometrial cancer patients and the controls. The level of 4-OHE2 was elevated in patients compared with the controls, while the levels of 2-MeOE1 and 2-MeOE2 were reduced in the endometrial cancer group. The results of this study indicate an imbalance of estrogen metabolites in endometrial carcinogenesis, and that the elevation of 4-OHE2 may be used as a potential biomarker for the risk assessment of estrogen-induced endometrial cancer.
Keywords: estrogens; 4-hydroxyestradiol; 2-methoxyestradiol; endometrial cancer; LC-MS